2019
DOI: 10.31235/osf.io/394w2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An introduction to Seshat: Global History Databank

Abstract: Seshat: Global History Databank, established in 2011, was initiated by an ever-growing team of social scientists and humanities scholars to test theories about the evolution of complex societies (Francois et al. 2016; Turchin et al. 2015). Seshat reflects both what is known about global history (within certain practical constraints, discussed below) and also what is unknown, or poorly known. Seshat is a continuously growing dataset incorporating evolving interpretations, highlighting persisting controversies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…Twelve cases were selected from the Seshat Databank (seshatdatabank.info), which assembles historical and archaeological information (e.g. archaeological site reports, primary and secondary historical sources, demographic data, and the like) to provide an archive of both raw and pre-coded data to test hypotheses about long-term cultural stability and change (Turchin et al, 2018, 2020). The Seshat Databank “World Sample 30” provides data for cultural sequences at 30 locations across the globe, selected to minimize autocorrelation and maximize cultural and environmental diversity (http://seshatdatabank.info/methods/world-sample-30/).…”
Section: Methodsmentioning
confidence: 99%
“…Twelve cases were selected from the Seshat Databank (seshatdatabank.info), which assembles historical and archaeological information (e.g. archaeological site reports, primary and secondary historical sources, demographic data, and the like) to provide an archive of both raw and pre-coded data to test hypotheses about long-term cultural stability and change (Turchin et al, 2018, 2020). The Seshat Databank “World Sample 30” provides data for cultural sequences at 30 locations across the globe, selected to minimize autocorrelation and maximize cultural and environmental diversity (http://seshatdatabank.info/methods/world-sample-30/).…”
Section: Methodsmentioning
confidence: 99%
“…The Seshat Project engages with academic historians and archaeologists, who are involved in the process in a number of ways, from helping design the codes being used, through to checking the data and helping with interpreting the patterns that emerge. Notably the process and our approach to data collection allows us to incorporate disagreements between academics about their interpretation of the past (see Turchin et al 2018 such that productivity in each is increased by growing them together. In our Oaxaca case study we have taken this into account by adjusting the yield based on the overall improvement in yield across all three crops.…”
Section: Discussionmentioning
confidence: 99%
“…The Seshat: Global History Databank is an interdisciplinary project aiming to codify archaeological and historical variables in order to allow comparative analysis of human social evolution (Turchin et al, 2015;François et al 2016;Turchin et al 2018). The databank currently features codified information on the past 10,000 years within thirty bounded geographic regions, termed Natural Geographic Areas (NGAs, selected to provide good geographic breadth as well as encompass a range of historical societies, from chiefdoms to empires.…”
Section: Historical and Archaeological Data On Agricultural Practicesmentioning
confidence: 99%
“…Finally, we would benefit from computational and quantitative scientists refining the statistical methods or offering alternative analytical approaches. The Seshat project has already demonstrated that such a transdisciplinary collaboration is both possible and fruitful by bringing together humanities scholars and social and quantitative scientists (Turchin et al 2019b). Our goal in this article is even more ambitious, insofar as we propose to expand the scale of this collaboration beyond the Seshat project to explicitly include a broader network of voices, including potential critics.…”
Section: Methods Overviewmentioning
confidence: 99%